PERANCANGAN PLTMH UNTUK MENDUKUNG WISATA HIJAU DI BENDUNGAN TAMBLANG, DESA SAWAN, KABUPATEN BULELENG - Edy Putra Dewantara, K Fajar; Setiawan, I.N.; Sukerayasa, I W (Program Studi Teknik Elektro UNUD, 2023)
The potential of water energy in Bali Province, especially in Tamblang Dam, is very high and can be utilized to provide energy needs in the surrounding area. On the other side, the Buleleng Regency Government took the initiative to develop tourism potential by planning a green tourism-based Tourism Destination Area (DTW), which utilizes renewable energy as a supporting component. One of the renewable energy potentials that can be utilized in Tamblang Dam is Micro Hydro Power Plant (PLTMH), which is designed with a designed flow rate of 2.21 m3/s with a capacity of 1.2 MW. The design of Micro Hydro Power Plant of Tamblang Dam requires an initial investment cost of Rp 2,434,358,091, and based on the results of economic analysis, the design of Micro Hydro Power Plant of Tamblang Dam is classified as feasible for investment, with NPV of Rp 68.6 billion, BCR 40.81, and PP less than 10 years.